2009
DOI: 10.1182/blood-2008-08-175828
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus colonization of tonsillar and peripheral blood B-cell subsets in primary infection and persistence

Abstract: Epstein-Barr virus (EBV) persists in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 52 publications
1
56
2
Order By: Relevance
“…In summary, although we had anticipated that EBV might be present in the numerically dominant transitional and naive B-cell populations in allo-HSCT recipients, the present data argue that EBV is restricted to CD27 1 memory B cells, just as in immunocompetent individuals. 18,20 This is not to deny that EBV can For personal use only. on May 9, 2018.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, although we had anticipated that EBV might be present in the numerically dominant transitional and naive B-cell populations in allo-HSCT recipients, the present data argue that EBV is restricted to CD27 1 memory B cells, just as in immunocompetent individuals. 18,20 This is not to deny that EBV can For personal use only. on May 9, 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Although posttransplant monitoring has led to an improvement in the early detection of patients at risk of developing PTLD, the pathophysiology of EBV reactivation in the context of allo-HSCT remains poorly understood. Given that memory B cells are the normal reservoir of EBV persistence in immunocompetent individuals, [18][19][20] we were particularly intrigued by existing reports in the literature that EBV reactivation following allo-HSCT usually occurs at a time when the newly reconstituting B-cell system consists predominantly of transitional and naive B cells. [21][22][23][24][25] To investigate this apparent paradox, here we have explored the relationship between immune reconstitution and EBV reactivation in a cohort of allo-HSCT recipients and ask whether the well-documented pattern of immune reconstitution [26][27][28] following allo-HSCT is perturbed in patients with high-level EBV reactivation.…”
Section: Introductionmentioning
confidence: 99%
“…IgD + CD27 + cells have been characterized as non-switched memory cells or marginal zone-like B cells (9,10). Healthy asymptomatic EBV carriers have low numbers of circulating EBV + B cells that are confined mainly to the IgD 2 CD27 + compartment but can also be found among IgD + CD27 + cells (11,12).…”
Section: E Pstein-barr Virus Infection Is Commonly Contracted Inmentioning
confidence: 99%
“…Cells with the latter latency types are invisible for the immune system. Other studies suggested that during IM, the different EBV latency types are generated without entering the germinal centers (11)(12)(13). However, the details of this transition are not completely known.…”
mentioning
confidence: 99%